Devolution in a multi ethnic society - Bastiampillai, Bertram; Wanasinghe, Shelton; Marga Institute (Colombo, Sri Lanka : Marga Institute, 1995)
With particular reference to Sri Lanka.
"Ethnic harmony programme."
Includes bibliographical references.
Keywords: Sri Lanka -- Ethnic relations; Sri Lanka -- Race relations